Factors affecting non-farm diversification among farm households in Jammu and Kashmir - Rakesh Nanda; Rajinder Peshin; Ashok K Singh; Lakshmi K Sharma; Yudhishther S Bagal (Agricultural Economics Research Review, 2023)
This article assesses the importance of non-farm activities and identifies factors that influence farm households’ participation in these activities in the Indian state of Jammu and Kashmir on the basis of a survey of 630 farm households in 2016-2017. The findings show that a majority of farm households are simultaneously engaged in non-farm activities, particularly in labour market and government services. Furthermore, the participation in non-farm activities is found to be positively influenced by education, family size, and dependency ratio, but negatively by farm size.